2022
DOI: 10.1111/1365-2664.14156
|View full text |Cite
|
Sign up to set email alerts
|

Thinning the thickets: Foraging of hardy cattle, sheep and goats in green alder shrubs

Abstract: Green alder shrubs Alnus viridis increasingly overgrow European mountain pastures but hinder natural forest succession. This nitrogen‐fixing, autochthonous invasive species has numerous negative effects including the loss of biodiversity and landscape aesthetic, eutrophication of soils and downstream waters, and greenhouse gas emission. Over centuries, A. viridis encroachment was impeded by grazing livestock, particularly goats. However, in modern agriculture, livestock numbers decreased on remote mountain pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Consequently, Highland cattle reduce workload needed for pasture management. Similar findings were presented for low‐productive Engadine sheep, consuming green alder shrubs in subalpine‐systems most efficiently and thereby hindering shrub encroachment and its numerous negative environmental effects (Pauler et al, 2022). Under low‐nutritive value diet, so‐called low‐productive cattle gain more weight than high‐productive cattle (Pauler, Isselstein, Berard, et al, 2020).…”
Section: Diversification Of Grazing Livestock and Herd Managementsupporting
confidence: 71%
“…Consequently, Highland cattle reduce workload needed for pasture management. Similar findings were presented for low‐productive Engadine sheep, consuming green alder shrubs in subalpine‐systems most efficiently and thereby hindering shrub encroachment and its numerous negative environmental effects (Pauler et al, 2022). Under low‐nutritive value diet, so‐called low‐productive cattle gain more weight than high‐productive cattle (Pauler, Isselstein, Berard, et al, 2020).…”
Section: Diversification Of Grazing Livestock and Herd Managementsupporting
confidence: 71%
“…For instance, Alberes cattle can feed year-round with a predominantly woody diet in Mediterranean forests of the Pyrenees (Bartolomé et al 2011 ). In the Alps, Dexter (Pauler et al 2022b ) and Highland (Pauler et al 2020 ; Svensk et al 2022 ) cattle are acknowledged to feed on woody species as well. The ability of certain livestock species and breeds to consume woody plants is linked with microbial populations in their rumen able to detoxify secondary metabolites and degrade lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Because A. viridis predominantly establishes on steep slopes and marginal locations, with few roads, the mechanical removal of this shrub species can be technically difficult, expensive and time consuming. One alternative and sustainable nature-based solution to counteract shrub encroachment could be the use of targeted grazing (Elias and Tischew, 2016;Elias et al, 2018;Pauler et al, 2022). Meisser et al (2014) monitored the grazing behavior of Hérens cows in A. viridis dominated pastures and showed that they did spend time in half or more encroached areas, despite their usual preference for open areas.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some robust livestock species and breeds have higher resistance to tannins, with ruminal bacterial populations that can better degrade lignified material, allowing them to feed on shrubs and digest their leaves (Berry et al, 2002;Marques et al, 2017). For instance, previous studies have shown that sheep and goats can efficiently feed on woody plants and significantly reduce their cover (Iussig et al, 2015;Álvarez-Martínez et al, 2016;Pauler et al, 2022). Some cattle breeds can also feed on shrub species (Zehnder et al, 2016;Pauler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation